STUDI FASIES DAN REKONSTRUKSI PENGENDAPAN BATUGAMPINGFORMASI RAJAMANDALA, KEC. CIBADAK, KAB. SUKABUMI. - Prayogi, Adi
The study area is located in the Cibadak region, Sukabumi, West Java Province. Geologically the area is located in the NE-SW major lineament what so called Cimandiri lineament. Along this lineament two limestone outcrops can be observe; one in the Rajamandala area, and the other in Cibadak area. Facies study and depositional reconstruction of Rajamandala limestone presented here is focused on three limestone outcrops, which are Pasir Bintang, Gunung Karang, and Bantar Muncang areas. Measuring sections has been conducted in those areas to record carbonate stratigraphic succession. About 30 limestones samples have been collected and prepare for carbonate thin analysis. Based on field observation and supported by petrographic analysis, five limestone facies can be identified. Which are; platy coral bindstone, massive coral boundstone, rudstone, well bedded larger foraminifera packstone to grainstone, and thick foraminifera wackestone facies. The massive coral boundstone to platy coral bindstone facies can be interpreted as reef-platform margin while the association of larger foraminifera packstonegrainstone, foraminifera wackestone and rudstone fasies outcropped at Bukit Pasir Bintang is interpreted as deeper depositional environment, which is; Slope and Toe of slope of a carbonat platform. The deeper facies are observes in the western part of the studied area while going southward the facies more representing shallow facies. At least, there are 2 (two) carbonate depositional cycle in study area, and it is characterized by rudstone facies as the boundary between them. Rudstone facies has become a sign for the end of keep-up phase a carbonate growth. First cycle had been started by larger foraminifera grainstone, thick bedded foraminifera wackestone-packstone, massive coral boundstone and it end-up by rudstone facies. The first cycle consist of start-up, catch-up, and keep-up phase. The second depositional cycle is characterized by platy coral bindstone, and thick bedded foraminifera packstone facies, with only start-up and catch-up phase.